(untitled) (Journal of Pharmaceutical Negative Results, 2023)
The study investigated managerial practices as predictors of achievement motivation of lecturers in Technical and Vocational Education and Training (TVET) Colleges in South-East Nigeria. Three research questions and three hypotheses guided the study. The study adopted a correlation research design. The study used 37 lecturers in TVET who were identified through the Achievement Motivation Scale. Two measuring instruments titled Managerial Practices Scale (MPS) and Achievement Motivation Scale (AMS) were used for data collection. Factor analysis was used to ascertain the validity of the instruments. The Eigen values are above 3.00 which showed that they can measure what they set to measure. The internal consistency reliability coefficient of 0.89 and 0.78 was ascertained for AMS and MPS using Cronbach alpha statistical method. Linear regression was used to answer the research questions while t-test associated with linear regression was used to test the hypotheses at 0.05 level of significance. Based on the findings of this study, the researchers concluded that managerial practices can predict achievement motivation among lecturers in TVET Colleges in South-East Nigeria to a reasonable extent. Specifically, managerial practice of organizing and organization predict achievement motivation among lecturers in TVET Colleges in South-East Nigeria to a very high extent while controlling can predict at a high extent. Based on the findings and conclusion of this study, the researchers recommended that: the school managers and administrators of TVET should carry out proper planning of the school programmes in order to get the lecturers motivated to achieve. The school authority should assign supervisors to any assigned responsibility in order to help in the organization of human and material resources needed to complete a set task. The school managers should be very active in controlling the process of achieving the set goals and objectives.